“Costume de casa vai à praia”?: uma análise da atitude e do comportamento sustentável do turista - Oliveira, Laís Vieira Castro (2018)
This study aims to analyze the attitude and the sustainable behavior of the tourist of Sun and Beach. In addition, the research aims to identify the degree of myopia, that is, the possible short-term view of consumers concerned only with their immediate personal satisfaction, without allying the possibility of present satisfaction with environmental sustainability in the long term. The research is characterized as quantitative, conducted through a survey with 188 tourists in the beach of Jericoacoara, Ceará, using for data collection the instruments of Pato (2004), Pato and Tamayo (2006) and Reinsberg and Vinje (2010). The results, statistically analyzed, showed that attitudes correlate significantly and positively with behaviors. It was also observed that Attitude - Ecocentric Belief and Habitual Sustainable Behavior have a positive effect on Sustainable Travel Behavior. In this way, it can be understood that the individual that presents Sustainable Behavior in their daily lives tends to extend it to diverse environments. However, in general, the tourists presented attitudes and behaviors that indicate myopia, that is, short-term vision, in relation to environmental sustainability issues.